Productivity and economic feasibility of cultivated forage and food crops in the central highlands of Ethiopia - Kebede, Gezahagn; Faji, Mulisa; Feyissa, Fekede; Mengistu, Gezahegn; Kehaliew, Aemiro; Mohammed, Kedir; Dejene, Mesfin; Geleti, Diriba; Minta, Muluneh; Balehegn, Mulubrhan; Boote, Kenneth J.; Dubeux, Jose Carlos B.; et al. (Frontiers in Animal Science, 2024)
The study was conducted to evaluate the yield performance of improved forage and food crops and to estimate the profitability of fodder and food crops in Holetta and Ejere areas, central highlands of Ethiopia during 2019 and 2020 cropping seasons. The experiment was laid out in randomized complete block design with three replications and evaluated two annual forage crops, two perennial forage crops, and two cereal food crops. Data on herbage dry matter (DM) yield was collected for forage crops while straw and grain yields were measured for food crops. Partial budget analysis was made to evaluate the economic feasibility of forage and food crops production. The result revealed that the herbage DM yield varied (P<0.05) at each location during each production year and combined over years and between the two locations. The straw and grain yields of food crops also varied (P<0.05) between the two production years and locations. The nutritive values of herbage and straw yields of forage and food crops differed (P<0.05) for all measured parameters. The crude protein and in-vitro dry matter digestibility of perennial forage crops were relatively higher than annual forage crops and straw of food crops. The partial budget analysis result indicated that the gross revenue (GR) and net return (NR) obtained from food crops were the highest followed by annual forage crops while the least was recorded from perennial forage crops during the first year of production. However, perennial forage crops produced the higher GR and NR than food crops and annual forage crops in the second year of production. In the second year of production, among the forage crops, Desho grass generated 308, 293, 287, and 232% while Rhodes grass generated 99, 92, 90, and 62% more NR than wheat, sole oat, barley, and oat/vetch mixtures, respectively. The benefit cost ratio (BCR) of perennial forage crops was the lowest in the first year of production but the ratio was the highest in the second year of production. This confirms the better economic feasibility of perennial forage crops as they can be maintained using minimal management cost once they have been established.